ANALISIS FAKTOR KINERJA PENGELOLAAAN AIR BERSIH PERDESAAN DI KABUPATEN BULELENG - Gede Suharjono; N. Budiartha R. M; Mayun Nadiasa (Master of Civil Engineering Program Study, Faculty of Engineering, Udayana University, 2014)
Provision of water supply in Buleleng regency handled by local water supply enterprice (PDAM) systems and swakelola systems which is done by the society in Facility Manager Unit/Facility Manager Community (UPS/KPS). Of the total 148 villages in Buleleng regency, only 68 villages have got PDAM systems, while 80 villages through a swakelola system by society. Based on the observations of the year 2010-2011 performance UPS/KPS tends to decrease. Performance degradation UPS/KPS will impact the disruption of the function of providing water to rural communities. The objective of this research is to knowing the factors that influenced the performance of Facility Manager Unit/Facility Manager Community (UPS/KPS) in supplying a rural water supply. This research used purposive sampling technique in which the subject of this research was taken from 67 of 80 village as a rural clean water manager. The respondent consist of ; one respondent from the apparatur in the village as a builder of SPAM (Drinking Water Supply System) in the village. Two respondents from the manager of UPS/KPS and there respondents from the society or custumers. The variable data is based on the measurement performance in public sector that consist of; input aspect, process aspect, output aspect, outcomes aspect and imfact aspect. The data from respondences will manage by using descriptive analysis and also factor analysis. The result of factor analysis showed that there was fives dominant factor that influenced the performance of UPS/KPS ; water spring debit, public willingness to pay, public awareness to pay, quality of service and ease of access to finance.